A conserved site on Ndc80 complex facilitates dynamic recruitment of Mps1 to yeast kinetochores to promote accurate chromosome segregation - Parnell, Emily J.; Jenson, Erin E.; Miller, Matthew P. (Current biology, 2024)
Accurate chromosome segregation relies on kinetochores carrying out multiple functions, including establishing and maintaining microtubule attachments, forming precise bi-oriented attachments between sister chromatids, and activating the spindle assembly checkpoint. Central to these processes is the highly conserved Ndc80 complex. This kinetochore subcomplex interacts directly with microtubules but also serves as a critical platform for recruiting kinetochore-associated factors and as a key substrate for error correction kinases. The precise manner in which these kinetochore factors interact and regulate each other’s function remains unknown, considerably hindering our understanding of how Ndc80 complex-dependent processes function together to orchestrate accurate chromosome segregation. Here, we aimed to uncover the role of Nuf2’s CH domain, a component of the Ndc80 complex, in ensuring these processes. Through extensive mutational analysis, we identified a conserved interaction domain composed of two segments in Nuf2's CH domain that form the binding site for Mps1 within the yeast Ndc80 complex. Interestingly, this site also associates with the Dam1 complex, suggesting Mps1 recruitment may be subject to regulation by competitive binding with other factors. Mutants disrupting this “interaction hub” exhibit defects in spindle assembly checkpoint function and severe chromosome segregation errors. Significantly, specifically restoring Mps1-Ndc80 complex association rescues these defects. Our findings shed light on the intricate regulation of Ndc80 complex-dependent functions and highlight the essential role of Mps1 in kinetochore bi-orientation and accurate chromosome segregation. [Display omitted] •Two segments of Nuf2’s CH domain recruit the Mps1 kinase to kinetochores•Other factors, including the Dam1 complex, also bind this “interaction hub”•Kinetochore-bound Mps1 promotes recruitment of the Dam1 complex•Association of Mps1 with the hub is essential for bi-orientation and cell viability Parnell et al. identify an “interaction hub” in the Ndc80 complex via mutational analysis in yeast, which associates with both Mps1 and Dam1 complex. Mutants at this site show inviability due to severe defects in bi-orientation and chromosome segregation; however, restoring Mps1-Ndc80c association rescues viability, highlighting its critical role.